If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9t + -5 = 4t + 10 Reorder the terms: -5 + 9t = 4t + 10 Reorder the terms: -5 + 9t = 10 + 4t Solving -5 + 9t = 10 + 4t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-4t' to each side of the equation. -5 + 9t + -4t = 10 + 4t + -4t Combine like terms: 9t + -4t = 5t -5 + 5t = 10 + 4t + -4t Combine like terms: 4t + -4t = 0 -5 + 5t = 10 + 0 -5 + 5t = 10 Add '5' to each side of the equation. -5 + 5 + 5t = 10 + 5 Combine like terms: -5 + 5 = 0 0 + 5t = 10 + 5 5t = 10 + 5 Combine like terms: 10 + 5 = 15 5t = 15 Divide each side by '5'. t = 3 Simplifying t = 3
| h=16t^2+14 | | -21-9h=-3(4h+5) | | [7+(-3)]+(-5)=7+[(-3)+(-5)] | | 30-7m+10-3m= | | 2x+2*2x+7=2x+7 | | -21-9h= | | (X+28)=(3x+14) | | 260-64-9= | | (2/7)÷N=(5/7) | | 9.8k+3.7=-0.22 | | a^2-4a+4-b^2= | | y=3e^5x | | 3/4(x-6)=2/8(x+2) | | y^2-16x-64=0 | | 38*x^3+19x^2-158=0 | | R=D-TforD | | .5x-2=.3x+1.2 | | -4c+3-6c=34 | | -x+4x=40 | | 2log(x-5)=6 | | Z/12=12/4 | | X/12=59/60 | | y=-3x^2-6(3)-5 | | 3/w=18/42 | | x^2+4m-12=0 | | N-3=20/8 | | 6x+2=4-(2x-5) | | n^3-n^2=6n | | 4-5+7-4k=0 | | x+16=2x-24 | | 5t-3t=18+3(1-t) | | 2xy=x-3y |